Pengembangan Podcast Natural Disaster Phenomena Berbasis Spotify sebagai Media Suplemen Pembelajaran Geografi - Pradika Adi Wijayanto; Vina Nurul Husna; Ervando Tommy Al Hanif; Andika Rizqy Heristama; Aulia Syafira Fitri (Universitas Indraprasta PGRI Jakarta, 2023)
Technological developments support the efficiency and effectiveness of geography learning. Learning during the pandemic was dominated by online systems that often used meeting-based applications combined with power point media. The above strategy has a weakness in the form of a large internet quota used, requires a stable signal and besides that learning cannot be done every time (real time), so it requires an alternative in the form of supplementary media, one of which is podcasts. The purpose of this research is to develop a spotify-based natural disaster phenomena podcast as a supplementary medium for learning geography. This research method is development research (R&D) using the Hannafin & Peck model. The subject of this study used a purposive sample by collecting data from semester 5 students who took disaster education courses at the Geography Department, Faculty of Social Sciences, Semarang State University for the 2021/2022 academic year. Quantitative data collection to determine the quality of media supplements developed using a questionnaire then data analysis techniques using percentage descriptions, while qualitative data were taken from validator and student perception questionnaires using the developed media supplements, qualitative data analysis techniques using data reduction, data display and conclusions. Based on data analysis, the quality of the podcast produced is good, but it is better if the media is better, it is able to make revisions according to the data suggestions and criticisms from the results of filling out the perception questionnaire (closed questionnaire).